P64 Is respiratory protective equipment effective in abolishing the work effect in patients sensitised to metal working fluid?. (12th November 2015) - Ilgaz, A; Moore, VC; Robertson, W; Robertson, AS; Burge, PS
Abstract : Background: Removing exposure to the causative agent in workers with occupational asthma or hypersensitivity pneumonitis is the main goal. The effectiveness of Respiratory Protective Equipment (RPE) in sensitised workers with usual exposures in their workplace is not known. We aimed to assess changes in serial peak expiratory flow (PEF) in workers with sensitisation to metal working fluid before and after the introduction of RPE. Methods: Workers who had been requested to keep 2-hourly PEF measurements before and after the introduction of RPE at a particular engine manufacturing plant were searched for on the Oasys PEF database. Those who had completed a minimum of 1 week before and after the introduction of RPE and had a positive area between curves (ABC) score for occupational effect from Oasys analysis (≥ 15 L/min/hr) on either record were included. All PEF measurements were made outside the working area where the RPE could be removed. Workers who remained symptomatic after cleaning and replacement of the metal-working fluid were only allowed to continue work if they complied with the strict use of respiratory protective equipment (RPE) using powered filtration and external changing facilities. Results: 19 workers fulfilled the inclusion criteria. The mean ABC score before RPE use was 27.85 L/min/hr (SD 17.69) and after RPE use was 19.65 L/min/hr (SD 22.77) showing a mean overall decrease of 8.20 L/min/hr (SD 28.60). 9 workers (47%) no longer showed an occupational effect on their PEF record once RPE was instated, 7 workers continued to show an occupational effect and 3 workers showed a new occupational effect which was not present before RPE use. Conclusion: Serial PEF measurements assessed with the ABC score from the Oasys system allowed quantification of the effect of RPE in sensitised workers. The RPE abolished falls in PEF associated with work exposure in 47% of workers, the remaining 10 workers had significant falls in PEF despite rigorously applied RPE. RPE should still remain a last resort in the hierarchy of control for occupational health.